A potent and selective small molecule inhibitor of myoferlin attenuates colorectal cancer progression. Issue 2 (7th February 2021) - He, Yuan; Kan, Weiqiong; Li, Yunqi; Hao, Yun; Huang, Anling; Gu, Haijun; Wang, Minna; Wang, Qingqing; Chen, Jinlian; Sun, Zhenliang; Liu, Mingyao; Chen, Yihua; et al.
Abstract: As a pivotal vesicular trafficking protein, Myoferlin (MYOF) has become an attractive target for cancer therapy. However, the roles of MYOF in colorectal cancer invasion remain enigmatic, and MYOF‐targeted therapy in this malignancy has not been explored. In the present study, we provided the first functional evidence that MYOF promoted the cell invasion of colorectal cancer. Furthermore, we identified a novel small molecule inhibitor of MYOF (named YQ456) that showed high binding affinity to MYOF (KD = 37 nM) and excellent anti‐invasion capability (IC50 = 110 nM). YQ456 was reported for the first time to interfere with the interactions between MYOF and Ras‐associated binding (Rab) proteins at low nanomolar levels. This interference disrupted several vesicle trafficking processes, including lysosomal degradation, exosome secretion, and mitochondrial dynamics. Further, YQ456 exhibited excellent inhibitory effects on the growth and invasiveness of colorectal cancer. As the first attempt, the anticancer efficacy of YQ456 in the patient‐derived xenograft (PDX) mouse model indicated that targeting MYOF may serve as a novel and practical therapeutic approach for colorectal cancer. Abstract : A novel and potent small molecule MYOF inhibitor (YQ456) exhibits anti‐growth and anti‐invasive effects against colorectal cancer with low toxicity. We first reveal the positive correlation between the expression level of MYOF and the metastatic potential of colorectal cancer. YQ456 interrupts the interactions between MYOF and Rabs (Rab7 and Rab32).